Basic consideration of a nuclear power monitoring system using neutron-induced prompt gamma rays. Issue 5 (3rd May 2020) - Okada, Koichi; Fushimi, Atsushi; Sekimoto, Shun; Ohtsuki, Tsutomu
ABSTRACT: Monitoring only neutron flux in a nuclear reactor core has an advantage of offering reactor power monitoring accuracy. We started the development of a new nuclear instrumentation based on the measurement of prompt gamma rays emitted from metals placed at the neutron flux monitoring positions. The thermal neutron flux at the position of each placed metal piece can be monitored by measuring the prompt gamma rays as the count rate of each energy. The gamma-ray energy range was limited from 6 to 10 MeV to mitigate the interference of environmental gamma rays. Four metals, Ti, V, Ni, and Cu, were chosen as candidates in consideration of their neutron emission rates and self-absorption. In an experiment with a high-purity germanium semiconductor detector, we considered the identification of individual peak energies in an assumed situation where prompt gamma rays were emitted from the four different metals at the same time. Energy resolutions of the peak with the largest energy gap from the nearest energy peak of the other candidate metals were smaller than the gap. Thus, we confirmed that at least one peak for each candidate metal was able to be separated from the peaks derived from other candidate metals.